TNFR2 expression predicts the responses to immune checkpoint inhibitor treatments - Liao, Ping; Jiang, Mengmeng; Islam, Md Sahidul; Wang, Yiru; Chen, Xin (Frontiers in Immunology, 2023)
Immune checkpoint inhibitors (ICIs) by targeting PD-1/PD-L1 or CTLA-4 have markedly improved the outcome of cancer patients. However, most solid tumor patients can’t benefit from such therapy. Identification of novel biomarkers to predict the responses of ICIs is crucial to enhance their therapeutic efficacy. TNFR2 is highly expressed by the maximally immunosuppressive subset of CD4+Foxp3+ regulatory T cells (Tregs), especially those present in tumor microenvironment (TME). Since Tregs represent a major cellular mechanism in tumor immune evasion, TNFR2 may be a useful biomarker to predict the responses to ICIs therapy. This notion is supported by our analysis of the computational tumor immune dysfunction and exclusion (TIDE) framework from published single-cell RNA-seq data of pan-cancer databases. The results show that, as expected, TNFR2 is highly expressed by tumor-infiltrating Tregs. Interestingly, TNFR2 is also expressed by the exhausted CD8 T cells in breast cancer (BRCA), hepatocellular carcinoma (HCC), lung squamous cell carcinoma (LUSC), and melanoma (MELA). Importantly, high expression of TNFR2 is associated with poor responses to the treatment with ICIs in BRCA, HCC, LUSC, and MELA. In conclusion, the expression of TNFR2 in TME may be a reliable biomarker for the precision of ICIs treatment of cancer patients, and this idea merits further research.